2017
DOI: 10.1002/anie.201708037
|View full text |Cite
|
Sign up to set email alerts
|

Alkynylation of C(O)–H Bonds Enabled by Photoredox‐Mediated Hydrogen‐Atom Transfer

Abstract: The development of new hydrogen-atom transfer (HAT) strategies within the framework of photoredox catalysis is highly appealing for its power to activate a desired C-H bond in the substrate leading to its selective functionalization. Reported here is the first photoredox-mediated hydrogen-atom transfer method for the efficient synthesis of ynones, ynamides, and ynoates with high regio- and chemoselectivity by direct functionalization of Csp2 (O)-H bonds. The broad synthetic application of this method has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(51 citation statements)
references
References 69 publications
0
49
0
2
Order By: Relevance
“…[1a, 23] Single-electron reduction of the resulting species would provide an azolium radical ion that, when coupled with an alkyl radical, would furnish synthetically valuable ketones (Scheme 1 D). Traditional methods for accessing acyl radicals, which are functionally equivalent to achiral azolium radicals, involve the use of aldehydes, [24] a-keto acids, [25] and others, [26] many of which suffer from significant drawbacks (i.e. toxicity, instability, superstoichiometric additive requirements, etc.).…”
Section: N-heterocyclic Carbenes (Nhcs) Have Emerged As Uniquementioning
confidence: 99%
“…[1a, 23] Single-electron reduction of the resulting species would provide an azolium radical ion that, when coupled with an alkyl radical, would furnish synthetically valuable ketones (Scheme 1 D). Traditional methods for accessing acyl radicals, which are functionally equivalent to achiral azolium radicals, involve the use of aldehydes, [24] a-keto acids, [25] and others, [26] many of which suffer from significant drawbacks (i.e. toxicity, instability, superstoichiometric additive requirements, etc.).…”
Section: N-heterocyclic Carbenes (Nhcs) Have Emerged As Uniquementioning
confidence: 99%
“…[2,3] Specifically,C (sp 3 )ÀHf unctionalization involving ah ydrogen-atom transfer (HAT) process driven by photoenergy is attractive due to the mild reaction conditions and high functional-group tolerance. [4] In combination with av isible-light photoredox catalysis, structurallyd istinct HATcatalysts, such as thiols, [5] thiophosphoric acids and imides, [6] quinuclidines, [7] sulfonamides, [8] chloride [9] and bromide [10] ions, aryl carboxylates, [11] and N-hydroxy compounds [12] wered eveloped. The currently-available HAT catalysts have limitations,s uch as:1)limited scope of cleavable CÀHb onds; [13] 2) catalystd ecomposition due to the inherent nucleophilicity [14] and/or reactivity with carbon-carbonm ultiple bonds; [15] and 3) insufficient stability, [16] thus leaving room for improvement.…”
mentioning
confidence: 99%
“…The reactionb etween N-Boc pyrrolidine (3a)a nd p-toluenesulfonyl cyanide (TsCN, 4a)i nt he presence of K 2 CO 3 produced cyanation product 5a in 56 %y ield (entry 1). When using previously reported HATc atalysts, such as quinuclidine (2b), [7] benzoic acid (2c), [11] and triisoproplysilylthiol (2d) [5] instead of 2a, 5a was obtained in low yield (entries 2-4). Further optimization of the reaction conditions improved the yield of 5a to 95 %w hen the catalyst loadings of 1 and 2a were reduced to 1a nd 5mol %, respectively,i nd ichloromethane solvent (condition B, entry 5).…”
mentioning
confidence: 99%
“…In 2017 Glorius et al reported the synthesis of ynones from aldehydes (Scheme ) . Photoredox‐mediated hydrogen‐atom transfer under blue light irradiation provided access to acyl radicals.…”
Section: C–c Bond: Sp2‐sp Disconnectionmentioning
confidence: 99%